Recommendation System on Knowledge Management System via OAI-PMH - Nyoman Karna; Iping Supriana; Nur Maulidevi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Knowledge Management System (KMS) might be a transformation from Library Management System (LMS). This transformation is possible when we add several knowledge processes from KMS not available in LMS. When a KMS is a transformation from a LMS, functionalities derived from librarian system will be also available in KMS. One of this functionality is recommendation system, where patron may receive related and recommended reading, usually based on subject similarity between knowledge documents. However, recommendation is delivered from system directly to patron. There is no recommendation from one system directly to another. This research proposes a communication model to provide recommendation from one KMS to another using LMS interoperability language, OAI-PMH. Although there is no real implementation, authors  hope  that  this  model  may  become  a basic reference for a better one. The novelty of this research is how to accommodate recommendation system between KMSs if the interaction is via knowledge sharing protocol, which in this research is OAI-PMH.